Ertapenem Supplemented Selective Media as a New Strategy to Distinguish β-Lactam-Resistant Enterobacterales: Application to Clinical and Wastewater Samples - Alexandre Bourles; Malia Kainiu; Damaris Ukeiwe; Nina Brunet; Camille Despaux; Antoine Biron; Ann-Claire Gourinat; Cyrille Goarant; Julien Colot (MDPI AG, 2023)
The increase in carbapenem-resistant Enterobacterales (CRE) is mostly driven by the spread of carbapenemase-producing (CP) strains. In New Caledonia, the majority of carbapenemases found are IMP-type carbapenemases that are difficult to detect on routine selective media. In this study, a culture-based method with ertapenem selection is proposed to distinguish non-CRE, non-CP-CRE, and CP-CRE from samples with very high bacterial loads. Firstly, assays were carried out with phenotypically well-characterized β-lactam-resistant Enterobacterales isolates. Then, this approach was applied to clinical and environmental samples. Presumptive CP-CRE isolates were finally identified, and the presence of a carbapenemase was assessed. In a collection of 27 phenotypically well-characterized β-lactam-resistant Enterobacterales, an ertapenem concentration of 0.5 µg·mL−1 allowed distinguishing CRE from non-CRE. A concentration of 4 µg·mL−1 allowed distinguishing CP-CRE from non-CP-CRE after nine hours of incubation. These methods allowed isolating 18 CP-CRE from hospital effluents, including the first detection of a KPC in New Caledonia. All these elements show that this cost-effective strategy to distinguish β-lactam-resistant Enterobacterales provides fast and reliable results. This could be applied in the Pacific islands or other resource-limited settings, where limited data are available.